2005
DOI: 10.1177/1420326x05060039
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic Bacteria and Filamentous Fungi Isolated from a Hospital Water Distribution System

Abstract: In recent years, hospital infections caused by opportunist micro-organisms in immunosupressed patients groups have become increasingly important. These micro-organisms grow easily in water distribution systems even to the extent of producing bio-film. In the present study the aim was to determine microbial populations in water samples collected from the distribution system of a big hospital. Water samples were collected from one hundred different points around the water distribution system in different section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In the present study, the deterioration of water quality through the distribution system was demonstrated and confirmed by Hapcioglu et al (2005). The deterioration includes the high counts in opportunistic pathogens.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, the deterioration of water quality through the distribution system was demonstrated and confirmed by Hapcioglu et al (2005). The deterioration includes the high counts in opportunistic pathogens.…”
Section: Discussionsupporting
confidence: 69%
“…There is no international standard method described for analyses of fungi in drinking water, hence several isolation procedures are used in the various studies preformed. Membrane filter techniques are mostly employed, applying volumes of 10-1000 ml water (Anaissie et al 2002b;Arvanitidou et al 1999;Doggett 2000;Gonç alves et al 2006b;Gonç alves et al 2006a;Hageskal et al 2007;Hapcioglu et al 2005;Hendrickx et al 2002;Hinzelin & Block 1985;Kanzler et al 2007;Nagy & Olson 1982;Niemi et al 1982;Ormerod 1987;Pires-Gonç alves et al 2008;Varo et al 2007;Warris et al 2001;Zacheus & Martikainen 1995). Another technique performed is direct plate-spread with volumes of 0.1-1 ml water (Franková 1993;Franková & Horecka 1995;Gö ttlich et al 2002).…”
Section: Limits In the Methodologymentioning
confidence: 99%
“…In the last decade, several more studies have resulted in increased knowledge on the occurrence of fungi in drinking water (Anaissie et al , 2002b(Anaissie et al , 2003Arvanitidou et al 2000;Gonçalves et al 2006a;Gö ttlich et al 2002;Hageskal et al 2006Hageskal et al , 2007Hageskal et al , 2008Hageskal 2007;Hapcioglu et al 2005;Kanzler et al 2007;Kennedy & Williams 2007;Panagopoulou et al 2002;Pires-Gonçalves et al 2008;Varo et al 2007;Warris et al 2001;Warris et al 2002). Some general results for all the studies performed are, for example, that the recovery of fungi varied between 7.5-89 % positive samples, and that the levels of fungi in the samples varied considerably in the various investigations.…”
Section: The History Of Fungal Water Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For definition of filamentous fungi, 100 µl diluted biofilm suspensions were spread-plated in triplicate onto Sabouraud Dextrose Agar plates with streptomycin and incubated 25 ºC for 14 d [19].…”
Section: Microbiological Analysismentioning
confidence: 99%